Prisoners' Anxiety Viewed from Types of Crime and Types of Prisoners - Rohisnawati, Rohisnawati; Santi, Dyan Evita (Empathy : Jurnal Fakultas Psikologi, 2023)
Kecemasan Narapidana ditinjau dari Jenis Kejahatan dan Jenis NarapidanaAnxiety is an instinctive fear of bad things happening in the future and is considered a major enemy. The aim is to find out whether there are differences in anxiety in terms of the type of crime and the type of prisoner. The total population in this study were 335 convicts in Class IIA. The author uses a quantitative method with a purposive sampling technique of 80 convicts. Validity test using Statistical Series Computing Program (SPS-2000). The results of the study indicate that there is a difference in anxiety in terms of the type of crime, with a description that the anxiety in inmates with the type of theft crime is higher than in the type of drug crime and there is no difference in anxiety in terms of the type of inmate. That is, there is not always a difference in anxiety between recidivists and non-recidivists because anxiety is also influenced by the maturity of individual personality and social environmental conditions, where human social interaction always carries out an attribution process that can affect the anxiety of other people in Class IIA.